Lignin-based materials : health care and medical applications - Joseph, Kuruvilla (Biomaterials science series, 2023)
Current environmental and energy concerns have led to lignin gaining increased attention in the last decade as a renewable biomass. Due to its structural and functional properties, such as antimicrobial behaviour, biodegradability, biocompatibility and ease of surface modifications, lignin-based materials have gained popularity in the biomedical field with applications ranging from tissue engineering scaffolds and wound dressing materials to drug delivery carriers. Using this book, the reader will learn about the chemistry of lignin, and the characterization, fabrication and properties of lignin-based composites with different matrices (thermosets, thermoplastics, elastomers etc.). In addition, the book illustrates how these materials are used in medical applications, covering drug delivery, wound dressing, tissue engineering, imaging, etc. Providing a neat overview of the current research for the biomaterials science community, this book is a one-stop resource for researchers and practitioners working on lignin-based biomaterials. For those active in the broader fields of materials science and biomedical engineering, this will be a useful reference and study aid.